Analisis Faktor Penghambat Penyusunan SPJ Pengeluaran Di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Kota Magelang - Silvia Melina Wati; Agustina Prativi Nugraheni (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2020)
Expenditure of Regional Working Unit (SKPD) are very related to every government agency. SKPD Expenditure is expenditure of funds use to finance office operational activities, where every expenditure must be equipped with complete and valid evidence that will be used for the process of preparing Accountability Letter (SPJ) Expenditure. Therefore, the author is interested to do the research that aims to find out and analyse the inhibiting factors for the preparation SPJ Expenditure. This research used descriptive qualitative method. The data source used in this study was primary data obtained directly from the Board of Investment Services and One-stop Permit Services of Magelang City. The results show that DPMPTSP of Magelang city has conducted the preparation of SPJ properly and on time, but there are still several inhibiting factors in the preparation of SPJ, namely the division of labor which each employee has concurrent position that results in employee performance not optimal and too many SPJ supplementary documents.